PENYESUAIAN DIRI PADA SANTRI BARU DI PONDOK PESANTREN - Hasanah, Muhimmatul (Universitas Muhammadiyah Gresik, 2024)
Background: Students' lives in pesantren are very different from their lives athome, and they need to adjust to survive until the end of the study period. Thestrict schedule has a further impact on children's lives. The many activities arealso a problem for some students to adjust to boarding school life. Objective: Thepurpose of the study is to find out how santri adjust to boarding school activities,as well as the types of behavior shown by new santri in adjusting to their newenvironment and boarding school activities. Method: This research uses a typeof qualitative research with a case study approach. Data analysis techniques usethe Miles and Huberman interactive model. Result: The results showed that newsantri need motivation from themselves, family, and the environment to be ableto adjust more easily. New students find it difficult to adjust only at the beginningof entering the dormitory. Conclusion: New students overcome this problem bybuilding good relationships with the dormitory environment such as makingfriends with fellow new students, administrators, and the surroundingcommunity.